2013
DOI: 10.1002/polb.23242
|View full text |Cite
|
Sign up to set email alerts
|

Miscibility in crystalline/amorphous blends of poly(3‐hydroxybutyrate)/DGEBA

Abstract: A differential scanning calorimetry (DSC) and smallangle X-ray scattering (SAXS) study of miscibility in blends of the semicrystalline polyester poly(3-hydroxybutyrate) (PHB) and amorphous monomer epoxy DGEBA (diglycidyl ether of bisphenol A) was performed. Evidence of the miscibility of PHB/DGEBA in the molten state was found from a DSC study of the dependence of glass transition temperature (T g ) as a function of the blend composition and isothermal crystallization, analyzing the melting point (T m ) as a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…For blends A and B, a shifting of the glass transition temperatures to lower values is registered as the content of TDP or MDP increases. An evident plasticizing effect, described in several polymer blends previously studied [32,[50][51][52][53], is observed, that is, the reduction of the Tg corresponding to the polymer component: the material becomes more flexible, improving the malleability for further use [6]. The LMWC acting as plasticizing increases the free volume between the polymer chains and so less energy is required to produce motion on chain segments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For blends A and B, a shifting of the glass transition temperatures to lower values is registered as the content of TDP or MDP increases. An evident plasticizing effect, described in several polymer blends previously studied [32,[50][51][52][53], is observed, that is, the reduction of the Tg corresponding to the polymer component: the material becomes more flexible, improving the malleability for further use [6]. The LMWC acting as plasticizing increases the free volume between the polymer chains and so less energy is required to produce motion on chain segments.…”
Section: Resultsmentioning
confidence: 99%
“…In the field of the polymer-LMWC blends, many works are focused on possible applications and not so much on the molecular characterization of interactions. LMWCs are added as additives to improve the properties of the polymeric component [6,[30][31][32][33][34][35][36][37]. Consequently, polymer-LMWC blends with different practical applications have been reported: controlled drug devices [38][39][40][41][42], regenerative medicine [43], electronic devices [44], hemodialysis applications [45], etc.…”
Section: Introductionmentioning
confidence: 99%
“…In a perfect lamellar structure it is assumed that L is equal to the sum of to the thickness of the amorphous ( l a ) or crystalline ( l c ) regimens but there is an inherent problem with the interpretation of the information obtained from SAXS originated from the principle of Babinet and in some cases, leads to an ambiguity in the allocation of the two main distances of a semi‐crystalline structure. Then considering that parameters l 1 and l 2 can represent l a or l c (depending on the sample) and that l c / L is the linear degree of crystallinity within the lamellar stacks, Φ l , the assignment of these parameters has to be done with the help of the bulk degree of crystallinity of the blends, Φ c , calculated from DSC measurements .…”
Section: Resultsmentioning
confidence: 99%
“…A homogeneous solution was observed at high temperature. A DSC study has demonstrated that this blend is miscible in the molten state …”
Section: Methodsmentioning
confidence: 99%
“…The authors have recently reported a study on miscibility and lamellar crystallinity in blends PHB/DGEBA . Following this line of research, the goal of this work was to obtain information about the crystallization and melting process in melt‐crystallized PHB/DGEBA blends through real‐time SAXS experiments and differential scanning calorimetry (DSC), studying, in particular, morphological changes in the lamellar structure and the melting and re‐crystallization process.…”
Section: Introductionmentioning
confidence: 99%